Minimally Invasive Total Hip Arthroplasty Using a Posterolateral Approach: Technique and Preliminary Results - Yu-Chuan Lin; Chung-Hwan Chen; Hsuan-Ti Huang; Jiing-Yuan Su; Yin-Chih Fu; Je-Ken Chang; Gwo-Jaw Wang (Kaohsiung Journal of Medical Sciences, 2007)
Minimally invasive total hip arthroplasty (THA) has become popular over the past few years. The advantages of this technique include reduced soft tissue damage. On the other hand, there are new risks related to reduced visualization. The widespread introduction of minimally invasive THA is still controversial. Here, we present our experiences and early results with a posterolateral approach to minimally invasive THA. Between August 2005 and July 2006, 85 hips from 79 consecutive patients were operated on using posterolateral minimally invasive THA. The outcomes were assessed on the basis of clinical and radiographic parameters. The mean operative time was 55 minutes. The mean length of hospital stay was 5.3 days. Average postoperative Harris hip score was 92.0 at 3 months postoperatively Complications included only one (1.18%) intraoperative nondisplaced calcar split. There were no cases of dislocation, neurovascular injury or postoperative infection. Our study indicates an early result of low complication rate and good functional recovery following minimally invasive THA using a posterolateral approach. This minimally invasive THA technique provides short-term safety and efficacy.